The Power of Words: Exploring Consumers' Perceptions of Words Commonly Associated with Agriculture - Joy N. Rumble; Jessica Holt; Tracy Irani (Journal of Applied Communications, 2014)
Individuals interpret words differently according to the experiences that have shaped their lives. As agricultural communicators, it is important to understand how individuals perceive certain words and if these perceptions influence their attitudes toward the agricultural industry. To better understand consumers’ perceptions, this study used focus group methodology to present words commonly associated with agriculture to consumer participants. Four focus groups were conducted over a period of two weeks. A total of 36 individuals participated in the focus groups. The results indicated some words activated participants’ attitudes and elicited a richer discussion. Divergent attitudes and perceptions were observed in the discussion of some words, while participants perceived other words similarly. For the agricultural industry to improve communications with consumer audiences, it is important to understand consumers’ existing perceptions of such commonly used descriptors.
Keywords: Framing; individual frames; focus groups; perceptions; qualitative research